Comparative Study of Balanced Nutrition Knowledge of Health Care in the Village and Sub-district of Kabila District Bone Bolango Regency - Inaku, Hartati (International Journal Papier Advance and Scientific Review, 2020)
Health cadres have responsibility for the local community and leaders appointed by the health center. They are expected to be able to carry out the instructions given by the supervisor in the work relationship of the health team. This article aims to examine the Comparative Study of Balanced Nutrition Knowledge of Health Cadres in the Village and Sub-district of Kabila District, Bone Bolango Regency. The type of research used in this research is comparative quantitative research with a cross-sectional study approach. The population in this study were all health cadres registered in the villages and sub-districts of Kabila District Bone Bolango Regency, as many as 72 health cadres. The sample size in the study was determined based on the Slovin method which was 42 samples. The results of the research were 17 health cadres in the village had sufficient knowledge of balanced nutrition (81.0%). Meanwhile, a small proportion of them had less knowledge of balanced nutrition, namely 1 person (4.8%). Most of the health cadres in the Sub-districts have sufficient knowledge of balanced nutrition, as many as 15 people (71.4%). Meanwhile, a small proportion of them had less knowledge of balanced nutrition, namely 2 people (9.5%). There is no difference in the level of knowledge of balanced nutrition among health cadres in the village and health cadres in the sub-district with a p value of 0.140.